Square peg, round hole? Programmed death-1 inhibitors in epidermal growth factor receptor-mutant non-small cell lung cancer - Gainor, Justin F. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Immune checkpoint inhibitors have emerged as powerful new agents in the management of advanced, non-small cell lung cancer (NSCLC). In particular, monoclonal antibodies targeting the programmed death-1 (PD-1) receptor and its ligand, PD-L1, have transformed treatment approaches for patients with advanced lung cancer. In a series of pivotal studies, the PD-1 inhibitors nivolumab and pembrolizumab and the PD-L1 inhibitor atezolizumab produced signi cant improvements in overall survival compared to standard single- agent chemotherapy in previously treated patients (1-4).